Alterations of Regional Homogeneity in Preschool Boys With Autism Spectrum Disorders - Lan, Zhihong; Xu, Shoujun; Wu, Yunfan; Xia, Likun; Hua, Kelei; Li, Meng; Liu, Mengchen; Yin, Yi; Li, Chunlong; Huang, Shumei; Feng, Ying; Jiang, Guihua; et al. (Frontiers in Neuroscience, 2021)
Objectives: The study was aimed at investigating the alterations of local spontaneous brain activity in preschool boys with autism spectrum disorders (ASD). Methods: Based on regional homogeneity (ReHo), the acquired resting state functional magnetic resonance imaging (fMRI) data sets, which included 86 boys with ASD and 54 typically developing (TD) boys, were used to detect regional brain activity. Pearson correlation analysis was used to study the relationship between abnormal ReHo value and the Childhood Autism Rating Scale (CARS), Autism Behavior Checklist (ABC), developmental quotient (DQ), and age. Results: In the ASD group, we found increased ReHo in the right calcarine, as well as decreased ReHo in the opercular part of the left inferior frontal gyrus (IFG operc), the left middle temporal gyrus (MTG), the left angular gyrus (AG), and the right medial orbital frontal cortex (mOFC) (p < 0.05, false discovery rate (FDR) correction). We did not find the correlation between the results of brain regions and the CARS, ABC, and age. Conclusions: Our study found spontaneous activity changes in multiple brain regions, especially the visual and language-related areas of ASD, that may help to further understand the clinical characteristics of boys with ASD.